Online interactions, trade and the gravity model - Constantin Bürgi; Zuzanna Studnicka (University College Dublin, UCD School of Economics, 2023)
We evaluate the drivers of online interactions and the importance of these interactions for international trade patterns. To this end, we measure the volume of online interactions between countries using a unique individual level data set with over 25 million multiplayer games played between December 2019 and August 2022 in the game Age of Empires II: Definitive Edition. We first show that, in line with the gravity model, distance is a crucial factor in determining the pattern of online interactions when trade costs are low or non-existent. This suggests that the distance effect in this environment captures additional factors such as cultural proximity. Subsequently, we use this interaction data as a new measure of cultural proximity and apply it to bilateral goods trade. We find that our measure is highly significant and reduces the importance of gravity variables, particularly the distance coefficient by around 10 %. It is also more important for diversified goods than homogeneous goods.
Keywords: F10; F14; Z10; 330; Gravity equation; services trade; online interactions